Analysis of weld defects and corrosion rates in SS304–SS400 dissimilar joints under various MIG welding positions - Yoggo Bagus Pamungkas; Nani Mulyaningsih; Sri Hastuti; R.Faiz Listyanda (Journal of Welding Technology, 2026)
The combination of SS304 stainless steel and SS400 low-carbon steel is widely used in the automotive and construction sectors because it combines weldability with good corrosion resistance. However, the differences in the physical and mechanical properties of these two materials have the potential to affect the quality of the welded joint, especially when considering variations in welding position. This study aims to analyze the effect of 1G, 2G, and 3G welding positions on welding defects and the corrosion rate of Metal Inert Gas (MIG) welded joints. The materials used were SS304 stainless steel plates and SS400 lowcarbon steel plates joined using a 60° V-groove. The welding process was performed using a current of 70 A as the primary parameter and ER309L electrode wire for all welding position variations. Welding defect testing was performed using the liquid penetrant method in accordance with ASTM E165 to detect surface defects, and corrosion rate testing was conducted using the electrochemical method in a NaCl solution, referencing ASTM G102 to determine the corrosion resistance of the welded joints. The test results showed that the 1G welding position produced the fewest welding defects compared to the 2G and 3G positions, and the 1G welding position yielded the lowest corrosion rate of 0.0789 mmpy, while the 2G and 3G positions showed corrosion rates of 0.1301 mmpy and 0.1699 mmpy, respectively. These values indicate that welded joints in the 1G position have better corrosion resistance compared to other positions. This difference is influenced by the stability of the weld pool, the effect of gravity, and the lower likelihood of weld defects in the 1G position. Thus, the welding position plays a crucial role in determining the quality and corrosion resistance of MIG weld joints in dissimilar materials, specifically SS304 stainless steel and carbon steel. SS400 low-carbon steel.